microRNAs Promoting Growth of Gastric Cancer Xenografts and Correlation to Clinical Prognosis - WEIDLE, ULRICH H. (Cancer Genomics Proteomics, 2021)
The annual death toll for gastric cancer is in the range of 700,000 worldwide. Even in patients with early-stage gastric cancer recurrence within five years has been observed after surgical resection and following chemotherapy with therapy-resistant features. Therefore, the identification of new targets and treatment modalities for gastric cancer is of paramount importance. In this review we focus on the role of microRNAs with documented efficacy in preclinical xenograft models with respect to growth of human gastric cancer cells. We have identified 31 miRs (-10b, -19a, -19b, -20a, -23a/b, -25, -27a-3p, -92a, -93, -100, -106a, -130a, -135a, -135b-5p, -151-5p, -187, -199-3p, -215, -221-3p, -224, -340a, -382, -421, -425, -487a, -493, -532-3p, -575, -589, -664a-3p) covering 26 different targets which promote growth of gastric cancer cells in vitro and in vivo as xenografts. Five miRs (miRs -10b, 151-5p, -187, 532-3p and -589) additionally have an impact on metastasis. Thirteen of the identified miRs (-19b, -20a/b, -25, -92a, -106a, -135a, -187, -221-3p, -340a, -421, -493, -575 and -589) have clinical impact on worse prognosis in patients.